US envoy's impressions of Lee Kuan Yew - Wei, Daniel Boon Chua (2015)
Lee Kuan Yew’s conversations with US leaders are not as widely known as his speeches. A report by a US ambassador to Singapore on Lee’s October 1967 visit to the United States reveals the extent of Lee’s successful diplomacy towards the US.